Fractional Corner Charges in Ionic Crystals: A Case Study of Sodium Chloride Using the DV-Xα Molecular Orbital Method - ISHII, Tomohiko; Takashita, Tomoko; Nishimura, Takaki; Sakane, Genta (Science and Technology Research Centre Universitas PGRI Semarang, 2026)
Recent theoretical predictions have revealed that even simple ionic crystals such as sodium chloride (NaCl) can exhibit fractional corner charges due to their topological characteristics. In this study, we employ the DV-Xα molecular orbital method to analyze the electronic structure of NaCl clusters in 1D, 2D, and 3D configurations. Cluster models were constructed with varying atomic numbers, and their highest occupied molecular orbitals (HOMOs), net atomic charges, and electrostatic potential maps were calculated. The results demonstrate that HOMOs are consistently localized on Cl 3p orbitals, showing a clear tendency for charge accumulation at the edges or corners, depending on the cluster dimensionality. Particularly in 3D models, the DV-Xα calculations explicitly confirmed the emergence of fractional corner charges of ±e/8, in agreement with topological insulator theory. This study highlights that even classical insulators like NaCl can exhibit topologically nontrivial electronic properties, challenging the conventional view of ionic crystals as topologically trivial. These insights may stimulate future computational and experimental research toward charge engineering and the design of sustainable ionic and functional materials that exploit charge localization effects.